THE IMPACT OF CRYPTO CURRENCY ON THE EVOLUTION OF BANKING SYSTEMS: A CASE STUDY OF FIRST BANK NIGERIA PLC - Smith, Daniel; Gonzalez , Maria; Wei , Liu (Ayden International Journal of Banking, Finance and Technology, 2024)
The study examined the effect of crypto currency on the development of Nigerian banking system with particular reference to the first bank Nigeria Plc. The study specifically examined the effect of Bitcoin (BTC) payment system and Litecoin (LTC) payment system, Ethereum (ETH) payment system and Bitcoin Cash payment system on the profit for the year of first bank Nigeria Plc. Data for the study was sourced through annual reports and accounts of first bank Plc for a period of 10 years, data collected were analysed using multiple regression analysis. Result of the analysis shows that Bitcoin (BTC) payment system has a positive and significant effect on the profit for the year of first bank Nigeria Plc. It was also observed that Litecoin (LTC) payment system has a negative significant effect on the profit for the year of first bank Nigeria Plc. The study further shows that that there is a negative effect of Ethereum on Profit for the year of first bank Plc. The study further indicates that Bitcoin Cash has a positive and significant effect on Profit for the year of firs bank Plc. Several financial regulatory authorities and institutions issued casual warnings to the general public, advising of the risks of involvement in digital currencies; however, digital currencies (especially cryptocurrencies) are thriving since the number of businesses and persons who accept them as payment are increasing by the day. A significant number of people are now fully convinced that the digital currency-Bitcoin is legitimate, safe and has value. "Bitcoin is going to be transformative" but unfortunately, since it is virtually untraceable it has been used for a host of nefarious purposes. Although, digital currencies may be very attractive to cybercriminals and fraudsters and present a host of new challenges to law enforcement in Nigeria, its adoption as a tool for national development in the digital age should be widely encouraged.